The Influence of Environmental Awareness, Knowledge, and Consumer Income on the Reduction of Plastic Shopping Bag Use - Achmad Tarmizi; Dian Meliantari (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Plastic waste has become one of the most critical environmental issues in Indonesia due to the increasing consumption of single-use plastic products, particularly plastic shopping bags. Excessive plastic usage contributes significantly to environmental pollution, as plastic materials require a very long time to decompose and can cause serious damage to terrestrial and marine ecosystems. Therefore, understanding the factors that influence consumer behavior in reducing plastic shopping bag usage is essential for promoting sustainable consumption. This study aims to analyze the influence of environmental awareness, consumer knowledge, and consumer income on the reduction of plastic shopping bag usage among students of Dian Nusantara University in Jakarta. This research employed a quantitative approach using a survey method, where data were collected through questionnaires distributed to 95 respondents. The data were analyzed using multiple linear regression with the assistance of SPSS software. The results show that environmental awareness, knowledge, and consumer income significantly influence the reduction of plastic shopping bag usage, both partially and simultaneously. Environmental awareness was identified as the most dominant factor affecting consumers’ behavior. These findings highlight the importance of strengthening environmental education, increasing public knowledge, and supporting sustainable consumption practices to reduce plastic waste and promote environmental sustainability.